Analisis Pelaksanaan Kegiatan Literasi dengan Program Gerli (Gerakan Literasi) yang Dikaitkan dengan Dongeng untuk Meningkatkan Minat Baca Siswa di SDN 1 Demulih - Ni Kadek Dwi Wulandari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to analyze the GERLI (Literacy Movement) Program which uses the storytelling method at SDN 1 Demulih to increase students' interest in reading. This research aims to assess the effect of a fairy tale-based literacy approach on improving students' reading abilities. The approach used is a qualitative descriptive method, with data collection through observation, interviews and documentation. The research results showed that before the program was implemented, students' interest in reading was low. However, after the program was implemented, there was a significant increase in students' participation and understanding of reading material, especially in terms of listening, composing stories, and discussions. As many as 85% of students were actively involved, showing higher enthusiasm for literacy activities. This program is considered effective in improving students' literacy skills, with recommendations that literacy activities be held regularly with a variety of more interesting stories, as well as involving parents to support a good reading environment at home.